Teaching Styles and Learning Facilities Influencing Student Motivation in English Learning - Asan, Stillman Miliam; Sri Wahyuni; Henrikus Joko Yulianto (Universitas Negeri Semarang, 2025)
This study investigates the influence of teaching styles and learning facilities on students’ motivation in learning English at the junior high school level in Banggai Regency, Indonesia. Drawing on Deci and Ryan’s (1985) Self-Determination Theory and Gardner’s (2010) Socio-Educational Model, this research adopts a mixed-methods design involving 60 eighth-grade students. Quantitative data were collected using structured questionnaires, while qualitative insights were obtained through semi-structured interviews with a total of twelve purposively selected participants.The findings reveal a significant positive relationship between facilitative teaching approaches and students’ intrinsic motivation. Classrooms equipped with adequate and functional learning facilities, such as audiovisual tools, digital learning media, and conducive physical environments, were also found to enhance students’ engagement and motivation levels. Interview results further underscore how autonomy-supportive teaching, interactive activities, and access to relevant learning resources can minimize anxiety and increase willingness to participate in language learning. The study highlights the synergistic effect between pedagogical approaches and the learning environment, indicating that even effective teaching practices may fail to produce optimal motivational outcomes in under-resourced settings. Practical implications are provided for educators, school administrators, and policymakers to support the integration of student-centered pedagogy and investment in school infrastructure to improve language learning outcomes. Limitations of the study include its restricted sample size and geographic concentration, suggesting the need for broader and longitudinal research to assess the generalizability and long-term impact of teaching styles and learning facilities on student motivation.